Defining the relationship between clinician-rated ECOG performance status and patient-reported health-related quality of life scores in men with metastatic hormone-naïve prostate cancer - Ikenna I. Nnabugwu; Eric N. Obikeze; Chinwe A. Nnabugwu; Solomon K. Anyimba; Okwudili C. Amu; Okezie M. Mbadiwe; Kevin S. N. Echetabu; Ijeoma L. Okoronkwo (Health and Quality of Life Outcomes)
Abstract Background Performance status and health-related quality of life (HRQoL) are important parameters in the management of metastatic prostate cancer. The clinician-rated Eastern Cooperative Oncology Group performance status (ECOG-PS) may not relate with the patient-reported HRQoL because the later puts into consideration some aspects of health that are not captured by the former. The aim of this study is to define the relationship between clinician-rated ECOG-PS and the patient-reported HRQoL in men with metastatic hormone-naïve prostate cancer (mPCa). Methods An analytical cross-sectional study recruiting patients presenting with mPCa in Enugu, southeast Nigeria. Two clinicians agreed on an ECOG-PS score for each study participant who in turn completed the Functional Assessment in Cancer Therapy – Prostate (FACT-P) and the EuroQol EQ-5D-5 L questionnaires with interviewer-assistance where necessary. Other medical information was retrieved from the records. ANOVA and chi-square tests were used to compare available data across ECOG-PS ratings and ordinal logistic regression was used to determine the FACT-P questionnaire items that related significantly with the ECOG-PS scores. Results Of the 224 participants (mean age: 70.62 ± 7.34), about 60.7% had ≥ 12years of formal education and 84.9% had ISUP grade ≥ 3 cancer. In all, 22.8%, 55.8%, 21.0% and 0.4% were ECOG-PS 1, ECOG-PS 2, ECOG-PS 3 and ECOG-PS 4 respectively. The mean FACT-P score, health utility index (HUI) and visual analogue scale (VAS) scores were 80.18 ± 17.56, 0.524 ± 0.324 and 60.43 ± 9.91% respectively. The FACT-P score (p = 0.002), HUI (p < 0.001) and VAS score (p < 0.001) varied significantly across the ECOG-PS ratings. Within the FACT-P, only questionnaire items GP3 (p = 0.024) and GP7 (p < 0.001) of the PWB domain, and items GF5 (p = 0.009) and GF6 (p = 0.003) of the FWB domain related strongly with the ECOG-PS categories. Conclusion There are indications that HRQoL questionnaire items that have to do with impairment in physical and role functioning relate strongly with ECOG-PS categories.